The effect of pH and salinity on the capability of marine microalgae biomass for removing Cd and Pb. Issue 1 (March 2020) - Lestari,; Permadi, S; Bayu, A; Sari, A A; Harmesa,; Yogaswara, D; Budiyanto, F
Abstract: The increase of heavy metals pollution requires a novel approach as an effective and eco-friendly removal strategy. The marine microalgae biomass was a strong candidate; however the study on local marine microalgae from Indonesia to be upgraded as metals biosorbent was limited. Thus, this study was aimed to utilize marine microalgae biomass as biosorbent for Cd and Pb removal in various pH and salinity value. The microalgae biomass was selected from diatomae, i.e. Chaeroceros sp., and Nitzschia sp., and green algae, i.e. Tetraselmis sp. The removal test was carried out at various pH and salinity range with initial metals concentration at 5 ppm and the measurement of metals concentration was utilizing Flame Atomic Absorption Spectrophotometer. The result exhibited the maximum Cd removal at pH 7 using Tetraselmis sp. (83.1%) and maximum Pb removal at pH 4 (85.4%) using Tetraselmis sp. and Chaetoceros sp. The removal of Cd and Pb was indicated a similar trend for the low removal capability at high salinity. Thus, this study revealed the best removal ability of the three marine microalgae was at pH 7 and low salinity.